الاختيارات الحديثية للإمام العدوي من خلال حاشيته – لقط الدرر بشرح نخبة الفكر - - الشين, مبروك; غريسي, محمد الحافظ (University of Eloued-جامعة الوادي, 2022)
"لقد تناول هذا البحث عدة موضوعات ضمن علم مصطلح الحديث، واستهدف البحث متن نخبة الفكر للحافظ بن حجر العسقلاني وكذلك حاشية الإمام العدوي بشرح هذا المتن، من خلال محورين رئيسين، أولهما :الخبر باعتبار وصوله إلينا. وثانيهما: نقد الراوي والمروي. وقد كان للإمام العدوي اختيارات بارزة عرضناها وناقشناها، وأوردنا رأي ابن حجر وطائفة من أقوال العلماء الذين توفرت لنا آراؤهم ورجحنا القول الذي رأيناه صوابا. ""This research dealt with several topics within the science of the term hadith, and the research targeted the text of the elite of thought by Al-Hafiz bin Hajar Al-Asqalani, as well as the footnote of Imam Al-Adawi, explaining this text, through two main axes, the first of which: the news, considering its arrival to us. The second: criticism of the narrator and the narrator. Imam Al-Adawi had outstanding choices that we presented and discussed, and we cited the opinion of Ibn Hajar and a group of scholars whose opinions were available to us, and we favored the saying that we saw as correct. "
مذكرة ماستر
Keywords: الاختبارات الحديثية، الامام العدوي، لقط الدرر بشرح نخبة الفكر; Hadith tests, Imam Al-Adawi, Katt Al-Durar, explaining the elite of thought